English vocabulary mastery of electrical engineering students at the State Polytechnic of Samarinda, Indonesia - Abdurrahim, Abdurrahim; Gunarto, Handri (Yayasan Mitra Persada Nusantara, 2024)
This study aimed to evaluate the English vocabulary mastery of Electrical Engineering students at the State Polytechnic of Samarinda. A descriptive research method was employed, focusing on assessing students' vocabulary knowledge through a standardized vocabulary test administered to 40 respondents. The data collected were analysed using descriptive statistics to determine the overall proficiency levels. The results indicated that the students’ mastery of English vocabulary was generally satisfactory, with most students achieving good scores. The study also identified several factors contributing to this achievement, including the students' interest in learning English, their active participation in classroom exercises, the effectiveness of the teaching methods used by lecturers, and the availability of supportive educational facilities, such as a language laboratory. These findings suggest that while the current level of vocabulary mastery is adequate, continued emphasis on these supporting factors could further enhance students' language proficiency, ultimately improving their academic and professional prospects.